The Comparison of the Emotional States of the Cancer Children to their Healthy Peers - Kiyan, Lugen Ceren; Durualp, Ender (International Journal of Child Health and Nutrition, 2019)
This study aimed to compare the emotional status of children with cancer between the ages of five and twelve with their healthy peers. The study groups of the research consist of children with cancer disease between the ages of five and twelve which have inpatient treatment at pediatric oncology service and healthy peers of the same age and gender. Totally 70 children, with 35 cancer who took inpatient treatment and two or more chemotherapy treatments between the dates September-November 2017, and also whose families accepted to participate in the research and 35 healthy children who live at the centre of Ankara, and were chosen with easy sampling method were included to the research. When collecting the data, “General Information Form” was used to determine the sociodemographic characteristics of the children and their families and the pictures drawn by the children were used to determine the emotional situations of the children. Pictures were evaluated according to the expert opinions using Koppitz’s “Draw a Man” evaluation test. The Chi-Square test was used to evaluate the data. The coherence between the experts was determined by the Cronbach Alpha value which was found 0.83. According to findings of the research, it was concluded that the impulsiveness, self-insecurity, anxiety, and anger-aggressiveness (p>0.05); shyness-timidity (p<0.05) of children with cancer was significantly higher than their healthy peers.